THE EFFECT OF SERVICE QUALITY IN ENHANCING CONSUMER SATISFACTION - Azis Nur Alamsyah (Universitas Islam Lamongan, 2023)
This article reviews the mechanism of sharia leasing, as well as its implementation in the joints of life. This review aims to provide an overview of the activities, mechanisms, and implementation of the sharia leasing mechanism through learning conducted at Muhammadiyah Purwokerto University in the Management Information System course. This type of research is qualitative research because it does not contain elements of numerical analysis and this research method is legal because the author chooses to use the National Sharia Council fatwa as a legal provision for solving the problem. The analysis and conclusions are based on the legal basis. In addition, the author also uses a series of books and literature related to the topic under review, including fatwas as data collection. The measuring instrument in this research uses DSN-MUI fatwas related to the topic, especially in knowing the law of leasing from the perspective of Islamic law. The process of implementation is reviewed on the system and mechanism of Islamic leasing that uses Islamic principles in it. The description and laws that apply in it show that this application is important to be considered and implemented by Islamic leasing. Therefore, a measuring tool is needed to find out which boundaries should be used in its implem entation.